Analysis of the potability of mineral waters consumed by the population of Jaraguá do Sul/Brazil - Stringari, Jessica; Tessila, Fernanda; Dams, Rosemeri Ines Ines; Dams, Rosemeri Ines; Sestile, Caio (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
Water, a natural resource of the Earth, is considered fundamental for human beings and must be in accordance with the quality parameters to be used in several purposes, however billions of people in the world do not have access to treated water, causing health problems. Therefore, this work aimed to evaluate the potability of still mineral water consumed by the population of Jaraguá do Sul, Santa Catarina, making a comparison with water samples from the distribution network and river water. Microbiological, parasitological, physical-chemical and phytotoxicity tests were carried out on all samples. In view of the results obtained, it was concluded that the samples of still mineral water consumed by the population of Jaraguá do Sul are suitable for human consumption and use, unlike the water in the distribution network and the river water, which showed significant divergences in several stages of the analyzes. For more accurate results and values, new tests and analyzes must be carried out, as well as the monitoring and inspection of the waters used by the population, in order to make a better diagnosis regarding their potability.